2006
DOI: 10.1051/0004-6361:20054476
|View full text |Cite
|
Sign up to set email alerts
|

Testing grain surface chemistry: a survey of deuterated formaldehyde and methanol in low-mass class 0 protostars

Abstract: Context. Despite the low cosmic abundance of deuterium (D/H ∼ 10 −5 ), high degrees of deuterium fractionation in molecules are observed in star-forming regions with enhancements that can reach 13 orders of magnitude, a level that current models have difficulty accounting for. Aims. Multi-isotopologue observations are a very powerful constraint for chemical models. The aim of our observations is to understand the processes that form the observed high abundances of methanol and formaldehyde in low-mass protoste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
228
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(276 citation statements)
references
References 29 publications
37
228
9
Order By: Relevance
“…Sakai et al (2009b) observed many deuterated carbon-chain molecules, and found that the deuterium fractionation ratios are moderate (2-7 %). The CH 2 DOH/CH 3 OH ratio is derived to be lower than 3 %, which is much lower than that found in hot corinos (Parise et al 2006). The observed ratios mean less degree of the CO depletion, which is consistent with the short time scale of the starless-core phase.…”
Section: Origin Of the Different Mantle Compositionssupporting
confidence: 68%
“…Sakai et al (2009b) observed many deuterated carbon-chain molecules, and found that the deuterium fractionation ratios are moderate (2-7 %). The CH 2 DOH/CH 3 OH ratio is derived to be lower than 3 %, which is much lower than that found in hot corinos (Parise et al 2006). The observed ratios mean less degree of the CO depletion, which is consistent with the short time scale of the starless-core phase.…”
Section: Origin Of the Different Mantle Compositionssupporting
confidence: 68%
“…2, we have plotted the [CH 2 DOH]/[CH 3 OD] ratio as a function of the luminosity of the protostars for all the sources (except G24.78+0.08) where this ratio has been measured so far. In addition to the present observations, we have thus included a sample of low-mass protostars (Parise et al 2006), as well as the hot-core Orion IRc2 (Jacq et al 1993 Parise et al (2006), while the data for Orion IRc2 is from Jacq et al (1993). The upper limit reported in Table 1 for G24.78+0.08 is not plotted because of the uncertain identification of the CH 3 OD line at 133.9254 GHz.…”
Section: Discussionmentioning
confidence: 99%
“…Parise et al 2006), a property observed in several other deuterated molecules in low mass protostars, although to a lesser extent (Ceccarelli et al 2007). This large deuteration very likely implies that, in low mass protostars, methanol was formed during the pre-collapse, cold, and dense phase.…”
Section: Introductionmentioning
confidence: 90%
“…Methanol deuteration is thus likely to be produced completely by active grain-surface chemistry, controlled by the atomic D content of the accreting gas. The high atomic D/H ratio required to account for the observed fractionation (0.1-0.2, Parise et al 2002) has been explained by invoking an efficient transfer of atomic deuterium from the HD main reservoir via the intermediate H 2 D + /D 2 H + ions (Roberts et al 2003;Parise et al 2006), which are very abundant in the CO-depleted pre-stellar gas (e.g., Caselli et al 2003;Phillips & Vastel 2003;Vastel et al 2004;Parise et al 2011). Presently, all the measured methanol deuterations have been satisfactorily reproduced by the most recent coupled gas-grain models (Taquet et al 2012;Aikawa et al 2012), Article published by EDP Sciences A27, page 1 of 8 thus supporting the hypothesis that D-fractionation in methanol is a distinctive relic of the protostars' past history.…”
Section: Introductionmentioning
confidence: 99%